MEMBANGKITKAN YANG HAMPIR MATI: KINERJA UPTD PASAR BINA USAHA DALAM MEMAJUKAN PASAR TRADISIONAL DI MEULABOH - Zakaria Zakaria; Alimas Jonsa; Vellayati Hajad (Universitas Teuku Umar, 2019)
UPTD Pasar is a technical implementer of the Trade Office in managing the Bina Usaha Market in Johan Pahlawan District, West Aceh Regency. This study looks at performance through the UPTD Market through productivity, service quality, responsiveness, responsibility, and accountability. The method used is descriptive qualitative through interviews with related sources such as the head of the Bina Usaha Market Unit, traders who sell at Bina Usaha Market, and the community as users or consumers at the Bina Usaha Market. The results show that the Market UPTD has been effective in managing the Bina Usaha Market Meulaboh because it has put forward the aspects of responsiveness, responsibility, and accountability that can be seen through achievements in the current performance of the UPTD Pasar. Good service results in satisfaction from market users. However, UPTD Pasar also still has shortcomings in terms of productivity and service quality. This can be seen from the lack of employees and supporting facilities in managing the Bina Usaha Market in Meulaboh.